METHYL ESTER OF {2-[2-CYANO-2-(4-NITROPHENYL)VINYL]PHENOXY}ACETIC ACID IN REDUCTION PROCESSES: UDC 546.65+535.37 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2018)
3-(Het)aryl-3-(2-alkoxyphenyl)acrylonitriles are very practical polyfunctional molecules for organic synthesis; in particular difficult objects with near placed active groups can be easy obtained by the reduction of 3-(het)aryl-3-(2-alkoxyphenyl)acrylonitriles fragments. But now only reduction of activated C=C bond in such molecules mostly investigated. Previously it was shown by us that the action of sodium borohydride on esters of {2-[2-cyano-2-(4-nitrophenyl)vinyl]phenoxy}acetic acid caused not only saturation of C=C bond but also reduction of ester group to alcohol. So the results of reduction of 3-(het)aryl-3-(2-alkoxyphenyl)acrylonitriles can be more interest when other electrophilic fragment presents in molecule. And the aim of current work is the investigation of methyl ester of {2-[2-cyano-2-(4-nitrophenyl)vinyl]phenoxy}acetic acid behaviour in different reductive medium.Because of the very high electrophylity of observed molecule it's unfeasible to obtain good result in reactions with strong nucleophyles or with chemical reduction agents; that's why the hydrogenation in mild condition was used on the first step. It was found that the nitro group and the activated C=C bond were reducted simultaneously by H2 at 1.2 atm presure and room temperature with Pd/C catalizing; so methyl ester of {2-[2-(4-aminophenyl)-2-cyanoethyl]phenoxy}acetic acid was formed. Further hydrogenation took place on higher H2 presure (80 atm); and as a result of the saturation of CºN bond methyl ester of {2-[3-amino-2-(4-aminophenyl)propyl]phenoxy}acetic acid creation occurred. The last compound can be transformed into 2-{2-[3-amino-2-(4-aminophenyl)propyl]phenoxy}ethanol by the LiAlH4 action. Such interesting structure also can be synthetized through the reduction of 3-[2-(2-hydroxyethoxy)phenyl]-2-(4-nitrophenyl)propionitrile that was obtained earlier: in the first step hydrogenation (1.2 atm H2) produced 3-[2-(2-hydroxyethoxy)phenyl]-2-(4-aminophenyl)propionitrile which nitrile group was reducted by LiAlH4 in the second step.
Keywords: methyl ester of {2-[2-cyano-2-(4-nitrophenyl)vinyl]phenoxy}acetic acid; 2,3-diarylpropionitrile; 2,3-diarylpropylamine; 2-aryloxyethanol